2007
DOI: 10.1017/s0954579407070083
|View full text |Cite
|
Sign up to set email alerts
|

Polyvictimization and trauma in a national longitudinal cohort

Abstract: This paper utilizes a national longitudinal probability sample of children to demonstrate how important exposure to multiple forms of victimization (polyvictimization) is in accounting for increases in children's symptomatic behavior. The study is based on two annual waves of the Developmental Victimization Survey that began with a nationally representative sample of children and youth ages 2 to 17. A broad range of victimization experiences were assessed using the 34-item Juvenile Victimization Questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
508
5
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 583 publications
(594 citation statements)
references
References 39 publications
61
508
5
20
Order By: Relevance
“…The authors of that study suggest that previously documented effects of maltreatment, when studied apart from other forms of childhood victimization, may partly be due to experiencing bullying victimization. Finkelhor et al (2007) argue that studying one form of childhood victimization in isolation may lead to an overestimation of its effects because of the large overlap among victimization experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of that study suggest that previously documented effects of maltreatment, when studied apart from other forms of childhood victimization, may partly be due to experiencing bullying victimization. Finkelhor et al (2007) argue that studying one form of childhood victimization in isolation may lead to an overestimation of its effects because of the large overlap among victimization experiences.…”
Section: Discussionmentioning
confidence: 99%
“…However, bullying victimization and other forms of violence are often studied in isolation, being the focus of separate research traditions, although we know that they often co-occur (Espelage, Hong, & Mebane, 2016; Wolke, Copeland, Angold, & Costello, 2013). Finkelhor, Ormrod, and Turner (2007) argue that focusing on one specific form of childhood victimization in isolation may lead to an overestimation of its effects because of the large overlap among victimization experiences. Studying bullying victimization without taking violence into account may therefore bear the risk of overestimating its association with potential negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experience of parental violence and unpredictability are individual factors relevant to severe sibling violence (2) . These children are polyvictimized (51) .…”
Section: Discussionmentioning
confidence: 99%
“…This is true for a number of other mental health concerns that predate the Internet, such as the complex relationship between substance use and psychiatric disorders, or victimization and depression (OÕMalley, 2003;Kilpatrick et al, 2003). Additionally, youth experiencing multiple forms of victimization may have more negative outcomes (Finkelhor, Ormrod, & Turner, 2007;Westenburg & Garnefski, 2003). A national study of children between the ages of 2 and 17 found those who had experienced four or more different kinds of victimization in a single year were more likely to have trauma symptoms, and when taken into account, greatly reduced or eliminated the association between individual victimizations and symptomatology (Finkelhor, Ormrod, & Turner).…”
Section: Problematic Internet Experiences and Co-occurring Mental Heamentioning
confidence: 99%